High Performance Flower Shape Manganese Oxide For Asymmetric Supercapacitor Device - Izan Izwan, Misnon; Baiju, Vidyadharan; R. A., Aziz; Rajan, Jose (Malaysian Technical Universities Network (MTUN), 2015)
A flower shaped manganese oxide have been synthesized using simple and low temperature procedure. Subsequently, an asymmetric supercapacitor is fabricated using manganese oxide and activated carbon as positive and negative electrode in aqueous electrolyte. The supercapacitor was measured at open windows 2.0 V showing energy density of 25.79 Wh/kg at power density of 100 W/kg. The supercapacitor stability was tested at 3 A/g and showing specific capacitance retention of 95% after 850 cycles